VD_FINDINFO HC / 2016 / 976 vom 10. Oktober 2016 - VD Tribunal cantonal (2016)
VENTE D'IMMEUBLE, DOLVICE DU CONSENTEMENT, ERREUR ESSENTIELLE, ACTE ILLICITE, TORT MORAL, FIANÇAILLES, ENRICHISSEMENT ILLÉGITIME, PRESCRIPTION, PÉREMPTION | 127 CO, 23 CO, 31 CO, 47 CO, 530 al. 1 CO, 67 al. 1 CO